Development of Beautiful Sunset Land (CSL) Beach to Realize a Sustainable Economy of It-Based Halal Culinary Tourism Enterprises - Nur'aini Nur'aini; Ahmad Hulaimi; Zaenafi Ariani; Nur fitri Hidayanti; Baiq Reinelda Tri Yunarni; Suci Canda Ati; Veni Edrian; Syahrul Ramadhan (Universitas KH. Abdul Chalim Mojokerto, 2024)
This study investigates the development of Pantai Cantik Sunset Land (CSL) as a halal culinary destination in Sekarbela District, Mataram City, focusing on the role of information technology (IT). Using SWOT analysis, surveys, and interviews, the research identifies significant potential for the halal culinary industry at CSL Beach. However, challenges include inadequate IT utilization in marketing, insufficient awareness of halal certification, and poor waste management. The findings suggest that enhanced IT use in social media, increased halal certification awareness, and improved waste management can boost the competitiveness and sustainability of halal culinary businesses at CSL Beach.